2009
DOI: 10.1007/s12094-009-0423-x
|View full text |Cite
|
Sign up to set email alerts
|

Radiosurgery and whole brain therapy in the treatment of brainstem metastases

Abstract: The combined treatment of SRS and whole brain radiotherapy treatment is effective in the control of BSM (only one patient died due to progression of BSM), improving the neurological symptoms in 41.9% of patients; therefore an early diagnosis and treatment is important. Many patients die due to causes other than the BSM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 10 publications
2
12
0
Order By: Relevance
“…(Table 4) and our overall survival was comparable to other studies. Relative to other studies that reported WBRT doses up to 45 Gy combined with SRS to the brainstem, the WBRT doses employed in our study were lower and hypofractionated [11, 12, 1719, 22, 23], but outcomes were similar to published series. The impact of WBRT dose on local control and toxicity when used in conjunction with brainstem SRS has not been investigated or reported previously.…”
Section: Discussionsupporting
confidence: 65%
“…(Table 4) and our overall survival was comparable to other studies. Relative to other studies that reported WBRT doses up to 45 Gy combined with SRS to the brainstem, the WBRT doses employed in our study were lower and hypofractionated [11, 12, 1719, 22, 23], but outcomes were similar to published series. The impact of WBRT dose on local control and toxicity when used in conjunction with brainstem SRS has not been investigated or reported previously.…”
Section: Discussionsupporting
confidence: 65%
“…To date, 14 series (a linear accelerator system was used in 5 series and a Gamma Knife in 9 series) have demonstrated the clinical efficacy of SRS for the treatment of brainstem metastases (Table 3). 4,7,8,10,[13][14][15][16]18,22,25,28,33,34 To the best of our knowledge, this is the first report based on a relatively large number of patients to describe GKS for brainstem metastases in which the focus was on neurological and qualitative survivals. These issues are crucial and should be given consideration in the management of patients with brain metastasis.…”
Section: Discussionmentioning
confidence: 95%
“…Although brainstem metastases have generally been regarded as a poor prognostic factor, some authors reported MSTs of more than 12 months-longer than those usually expected in patients with brain metastases. 4,22 Recent advances in cancer treatment, as well as in SRS, which allow radical treatment of brain metastases, may have contributed greatly to prolonged overall survival. Nowadays, approximately 90% of patients with brain metastasis die as a result of progression of the systemic disease.…”
Section: Overall Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of reports have described the treatment of brainstem metastasis, including pontine metastasis ( 1 11 ). The most common site of primary malignancy in patients with metastases to the brainstem is the lungs; the majority of such malignancies are adenocarcinomas ( 6 , 7 , 9 , 10 ) and, less commonly, squamous cell carcinomas ( 8 ). SRS is the preferred treatment option for brainstem metastases due to its provision of adequate local control with low morbidity.…”
Section: Discussionmentioning
confidence: 99%